2021
DOI: 10.1557/s43577-021-00116-1
|View full text |Cite
|
Sign up to set email alerts
|

Thread-based wearable devices

Abstract: One-dimensional substrates such as textile fibers and threads offer an excellent opportunity to realize sensors, actuators, energy harvesters/storage, microfluidics, and advanced therapies. A new generation of wearable devices made from smart threads offer ultimate flexibility and seamless integration with the human body and the garments that adorn them. This article reviews the state of the art in thread-based wearable devices for monitoring human activity and performance, diagnoses and manages medical condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…[ 75 ] In contrast, the polymers/plastics with hydrophilic functional groups (e.g., carboxyl or amino) exhibit hydrophilicity, including polyethylene terephthalate (PET), [ 95 ] polyimide (PI), [ 96 ] and polyurethane (PU). [ 97 ] Moreover, the porous substrate materials (e.g., paper, [ 98 ] textile, [ 99 ] and silk [ 100 ] ) can even provide active liquid wicking.…”
Section: General Surface Wettabilitymentioning
confidence: 99%
“…[ 75 ] In contrast, the polymers/plastics with hydrophilic functional groups (e.g., carboxyl or amino) exhibit hydrophilicity, including polyethylene terephthalate (PET), [ 95 ] polyimide (PI), [ 96 ] and polyurethane (PU). [ 97 ] Moreover, the porous substrate materials (e.g., paper, [ 98 ] textile, [ 99 ] and silk [ 100 ] ) can even provide active liquid wicking.…”
Section: General Surface Wettabilitymentioning
confidence: 99%
“…Furthermore, cellulose materials such as threads [25]- [31], cloths [17], [32]- [34], and sponges [35]- [39] can be utilized for capillary driven force in microfluidics. Garg et al reported a printed textile for reusable SERS substrate.…”
Section: Biocellulose-based Componentsmentioning
confidence: 99%
“…The flow characteristics and the detection methods employed in threads are similar to those employed in paper, since both are porous (Berthier et al, 2017;Tan et al, 2021). However, compared to paper devices, thread-based devices are more suitable for wearable applications since threads can be used to create clothing either by directly sewing, or having walls patterned onto cloth (Xiao et al, 2019;Tan et al, 2021;Xia et al, 2021).…”
Section: Thread-based Analytical Devices(µtads)mentioning
confidence: 99%
“…Moreover, barcode detection can provide results of multiple analyte reactions (e.g., blood typing) that otherwise are difficult to achieve (Nilghaz et al, 2014). For a comprehensive review on thread devices, the readers are encouraged to read the suggested references: (Farajikhah et al, 2019;Weng et al, 2019;Tan et al, 2021;Xia et al, 2021).…”
Section: Thread-based Analytical Devices(µtads)mentioning
confidence: 99%